Algoritmo de controlador PID sintonizado pelo método de produto interno e embarcado em CLP com uso da plataforma de simulação CodeSys - VERAS, Bianca Fontenele Lemos (2023)
Control systems with Proportional, Integral and Derivative (PID) actions are frequently used in industrial processes and in recent years techniques that simulate the implementation of optimal-adaptive controls in plants in the mining sector have been proposed as efficient tuning methods. As for the control performance embedded in Programmable Logic Controllers (PLC), it is still under explored, which promotes the importance of discussing control implementations in PLC. In this article, we present the simulation of a PID control system embedded in a PLC, designed in the CodeSys simulation and development software for application in a real plant of the operational process of unloading solids in grains by Car Dumper (CD). In the mining industry, the flow control of bulk solids in CD is done, most of the time, by varying the speed of the feeders by changing the frequency of inverters, which is manually configured with the insertion of commands in a Human Machine Interface (HMI). The use of the tuning technique of PID controllers by Internal Product is presented in order to facilitate the parameters’ configuration of the PID controller gains applied to the control of the solid flow in the unloading by CD, guaranteeing more assertiveness in the tuning process and in this way improving the speed control process of the VVs to reach the desired flow.